Penggunaan Desain Model Pembelajaran Assure Berbasis Multimedia dalam Meningkatkan Hasil Belajar Fiqih di Sekolah Tahfidz - Syahputra, Eka Bayu; Putra, San (Education Achievement: Journal of Science and Research, 2025)
Fiqh learning in tahfidz institutions often faces challenges such as low student participation and understanding due to monotonous teaching approaches. This study aims to describe the implementation of the ASSURE instructional design model based on multimedia to improve fiqh learning outcomes at the Tahfidz Quran Foundation Raudhatul Hasanah Mulyorejo. This research employed a qualitative field research approach, with data collected through observation, interviews, and documentation. The subjects consisted of one fiqh teacher and 20 tahfidz students selected purposively. The findings indicate that the use of interactive multimedia, such as animated videos and the Kahoot quiz application, effectively enhances conceptual understanding of fiqh, encourages active participation, and creates a more engaging learning environment. Students showed increased interest, greater involvement, and improved ability in religious practice. This approach also supported teachers in delivering material in a more structured and engaging manner. These results suggest that integrating technology into religious learning can serve as an innovative and effective alternative in Islamic educational settings, particularly in tahfidz schools.